Substituting Soybean Meal with Fermented Leaves and Seeds of Rubber Trees (Hevea brasiliensis): Effects on Carcass Percentage, Abdominal Fat Percentage and Meat-to-Bone Ratio in Broiler Chickens - Syahruddin , Erman; Herawaty, Rita; Azhar (International Journal of Poultry Science, 2019)
Objective: This study aimed to reduce the use of imported feed ingredients and those competing with human food resources by using local conventional feed. Materials and Methods: This study included 480 day-old caged broiler chicks of the Cobb strain. Chicks were housed in colonies in wire cages. Each cage unit was equipped with a feeding area, a drinking area and an incandescent lamp. A completely randomized design with 6 treatments and 4 replications was employed. The data obtained were analysed using ANOVA and differences between treatments were tested by Duncan’s multiple range test (DMRT). Treatments included a group fed control rations as well as groups fed FLSRT as a replacement for specific percentages (0, 20, 40, 60, 80 and 100%) of soybean meal. The observed variables included body weight gain, carcass percentage, meat-to-bone ratio, percentage of abdominal fat, percentage of ventricular weight and thickness of broiler chicken intestine. Results: The results showed that replacement of up to 80% of soybean meal protein with processed rubber leaves and seeds in broiler rations had no significant effect (p>0.05) on body weight, carcass percentage, or meat-to-bone ratio. However, measurements of these parameters under replacement with 100% processed rubber leaves and seeds differed significantly (p<0.01) from other treatments. Conclusion: Replacement of up to 80% of soybean meal with FLSRT resulted in increased body weight, higher carcass percentage and meat-to-bone ratio and a lower percentage of abdominal fat in comparison to replacement at the 0% concentration.